An Experimental Evaluation of using Waste Cooking Oil Biodiesel in a Diesel Engine. Issue 12 (26th November 2013) - El‐Adawy, M.; Ibrahim, Amr; El‐Kassaby, M. M.
Abstract Waste‐cooking‐oil biodiesel has a great potential to be widely used as an alternative, renewable fuel for diesel engines in the near future. The aim of this investigation was to experimentally study the effect of using different blends of waste‐cooking‐oil biodiesel and diesel fuel on the diesel‐engine performance, combustion characteristics, and emissions. It was found that increasing the percentage of biodiesel in the fuel blend from 0 to 50 % decreased engine torque and thermal efficiency by 9 and 11 %, respectively, for an engine speed of 1500 rpm. On the other hand, the engine fuel consumption increased by 17 %. In addition, the CO and HC emissions decreased by 31 and 40 %, respectively, whereas CO2 and NOx emissions increased by 17 and 40 %, respectively. It was also found that the ignition delay period decreased and the total combustion duration increased with increasing percentage of biodiesel in the fuel blend.